How Can Cooperative Learning Lead EFL Sixth Graders to Use English Orally? (2016)
ABSTRACT: This action research project was developed with 31 EFL sixth graders at a private school in Colombia. It aimed to analyze if cooperative learning could lead students to use English orally. The jigsaw was used for 3 weeks with different stories. Data gathered were from class observations, students’ self-evaluations and surveys, and a teacher journal. Findings showed that students used English in different ways and they felt more comfortable. Factors helping them were adopting new roles, using Spanish before English for comprehension and production, and having direct teacher and university advisor intervention to check understanding and to encourage use English. Difficulties were related to increased noise and an unequal distribution of material in larger groups.